Implementasi Akuntabilitas Pada Organisasi Pengelola Zakat (Studi Kasus : Baznas Kabupaten Agam) - Bella Kurnia Putri; Wiwik Andriani; Rasyidah Mustika (Jurusan Akuntansi Politeknik Negeri Padang, 2016)
Zakat is an alternative that can be utilized in poverty reduction. Zakat is expected to minimize the income gap between the rich and the poor. Therefore, zakat management organizations are required to become accountable institutions. This is because funds managed by the zakat management organization are people's funds. This study aims to determine the implementation of accountability in National Zakat Agency (NZA) Agam Regency. The accountability principle used is the principle stated by the Humanitarian Forum Indonesia (HFI) and the Public Interest Research Advocacy Center (PIRAC). Data is collected through interviews, document review and observation. Analysis of the data used is thematic analysis. The results showed that NZA of Agam Regency had implemented a good management of testes. However, the application of the principle of accountability has not been maximized so that it still needs to be improved. It is expected that NZA of Agam Regency can maximize the application of the principle of accountability in the future.